Voluntary Environmental Regulation, Innovation and Access to Finance in Moroccan Firms: Revisiting Porter’s Hypothesis - Mansouri, Rim; Tounsi, Said (International Journal of Energy Economics and Policy, 2025)
This paper investigates the effects of voluntary environmental regulation on innovation in Morocco, a country engaged in an ambitious environmental transition. Using data from the 2023 World Bank Enterprise Survey, we analyze the impact of two types of environmental practices—energy management and CO2 emissions monitoring—on firms’ decisions to invest in Research & Development (R&D). To assess the role of financial constraints, we estimate our model separately for sub-samples of firms with and without access to external financing. The results indicate that energy management is positively associated with a higher probability of investing in R&D, while CO2 emissions monitoring has no significant effect. Furthermore, access to finance does not enhance the effect of environmental practices on innovation. These findings provide new empirical evidence on Porter’s hypothesis in a developing economy, highlighting that the driver of innovation is the adoption of specific, efficiency-oriented practices, and that this mechanism operates independently of firms’ access to external capital.